Organisasi Advokat Pasca Surat Ketua MA Nomor 73/KMA/HK.01/IX/2015 - Alhadi, Muhammad Nurcholis (Lex Librum : Jurnal Ilmu Hukum, 2024)
The division among the lawyer organizations has led them to claim themselves as the leaders of the organization. This division also affects who has the right to appoint and swear in lawyers. The letter from the Chief Justice of the Supreme Court Number 73/KMA/HK.01/IX/2015 has provided a new direction in the management of the advocate organization in Indonesia. This letter reaffirms the principle of non-intervention by the Supreme Court in internal disputes of the law organization while also strengthening the principle of independence in the legal profession. However, the impact has given rise to various interpretations regarding the structure and regulation of the ideal lawyer organization. This research aims to analyze the impact of the letter on the dynamics of the lawyer organization, both from legal, institutional, and professional aspects. Through a juridical-normative approach and analysis of secondary data, this research identifies the challenges and opportunities faced by advocacy organizations following the issuance of the letter. The research findings indicate that this letter encourages lawyer organizations to be more independent in resolving internal conflicts, but on the other hand, it creates doubts about the mechanisms of oversight and professional accountability. Therefore, it is necessary to strengthen regulations that can bridge the interests of the parties to maintain the integrity of the legal profession in Indonesia.